ILRI 40 years remarks by Alice Avedi, Second Counselor, Kenyan Embassy to Ethiopia - Avedi, A. (International Livestock Research Institute, 2014)
Remarks from Alice Avedi, Second Counselor, Kenyan Embassy to Ethiopia on behalf of Catherine Mwangi, Kenyan Ambassador to Ethiopia (representative of an ILRI founding institution) at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives. ILRI@40 conference, Addis Ababa, Ethiopia, 6–7 November 2014.